New technologies and machines for stereotactic radiation therapy - Brian Wang; Jun Yang (Precision Radiation Oncology, 2022)
Abstract Stereotactic radiosurgery and stereotactic body radiation therapy have been increasingly utilized in radiation oncology to treat early stage tumors, metastatic targets, and retreatment of relapsed diseases due to their efficiency, treatment effect, and cost effectiveness over the past two decades. Stereotactic radiosurgery and stereotactic body radiation therapy both demand high specifications for their delivery machines, as they deliver radiation doses with fewer treatment fractions and higher doses per fraction. Manufacturers have either invented specialized technologies solely or customized their existing machines for this purpose. In this paper, we review the major technologies and treatment machines for stereotactic radiosurgery and stereotactic body radiation therapy, describe their main features, and discuss the advantages and disadvantages.